The intellectual history and rabbinic culture of medieval Ashkenaz - Kanarfogel, Ephraim (Wayne State University Press, 2012)
This book challenges the dominant perception that medieval Ashkenazic rabbinic scholarship was lacking in intellectualism or broad scholarly interests. While cultural interaction between Ashkenazic Jews and Christians in western Europe was less than that of Sephardic Jews, the author's study shows that the intellectual interests of Ashkenazic rabbinic figures were much broader than Talmudic studies alone.